Effect of Ploughing Depth, Tractor Forward Speed, and Plough Types on the Fuel Consumption and Tractor Performance - Kareem Ibrahim Kareem; P. Sven (Polytechnic)
Cost of fuel has a significant impact on the input costs of agricultural production, especially during primary tillage. It is affected by several parameters including tractor forward speed, depths of ploughing, and plough types. The experiment was performed in a Soil Hall at Harper Adams University, United Kingdom, in April 2015. A Massey Ferguson 8480 4WD tractor was used for investigating objectives of this study. The experiment was performed in a sandy loam soil texture at 11.73% soil moisture content and 1.35 (g/cm3) dry bulk density to study the amount of fuel consumption (l/ha) and the performance of tractor with effect of moldboard and disc ploughs as ploughs type, 15 and 20 cm as ploughing depth and 5 and 7 km/h as tractor forward speeds. The results showed that fuel consumption with a disc plough 5% was higher compared to the moldboard. Fuel consumption decreased approximately 8% when tractor at 7 km/h. Fuel consumption significantly decreased about 34% when ploughing depth increased from 15 to 20 cm. The power requirement to operate moldboard plough was higher by about 14% than a disc. The power requirement at speeds of 7 km/h was higher compared to the speeds of 5 km/h by about 27%. When the depth of ploughing increased from 15 to 20 cm, the power requirement increased by about 1.5%.